Translating Poetry in Sign Language: An Embodied Perspective - Raniolo, Erika (Frontiers in Communication, 2022)
In the translation into sign language, where does the ≪sense≫ reside and how can it be constructed in the target language? To what extent does the orality of sign languages, intended as the absence of a writing system, affect the translation process? What role do the characteristics of sign languages, first and foremost iconicity, play? The issues we address in this study are placed at the crossroads between sign language linguistics and translation studies, thanks to the awareness that both disciplines have, respectively matured in recent decades. As regards the linguistics of sign languages, we refer to the semiological model proposed by Cuxac and colleagues. On the subject of translation studies, our main reference is represented by Meschonnic, according to whom the sense is found in the ≪rhythm≫ (understood as form). Analyzing the translation process, and more specifically the poetic translation, allows us to observe the centrality of the body. We take into account the perspective of embodied cognition, based on the link between the language and the sensorimotor system. Therefore, we question the role of the body in the construction of the sense: the body is considered above all in its sensorial dimension, in its being an entity that perceives and enters into a relationship with the world. That makes us hypothesize a synesthetic construction of the sense. In order to follow in practice what is stated theorically, we present one of our translations: the translation into LIS of a poem in Italian, L'Infinito by Giacomo Leopardi. The translation into sign language makes it possible to observe the role of corporeality in the process of re-enunciation of sense.